Variasi Bahasa Dalam Film Keluarga Cemara: Kajian Sosiolinguistik - Latifa, Zuhra; Frantiko, Dika; Qomariyah, Laili Nur (Deskripsi Bahasa, 2024)
Language and age is a sociolinguistic realm that discusses how language can distinguish a person's status in the context of age. Differences within human groups often arise due to age, which can give rise to variations in social dialects and provide distinctive characteristics within certain communities. This study tries to reveal the role of age in determining the use of language in the speech of characters in the film Keluarga Cemara. This research was conducted with a sociolinguistic approach using qualitative descriptive methods. This study found that language can distinguish humans into four groups: children, adolescents, adults, and the elderly. Language in children is characterized by word shrinkage and has a characteristic sound. In adolescence language has begun to vary and unique, adolescents are accustomed to presenting new languages that are created based on the results of their creativity. In adulthood is a phase when language begins to improve, because of its authority as an adult regularity, linguistic rules begin to be considered. In the elderly, communication competence begins to be low and turns into topics about medicine and physical.